“RAVEN’S LAND”: THE EARLY INDIGENOUS HISTORY OF THE CROWSNEST & WATERTON LAKES: MISSING AND MURDURED INDIGENOUS WOMEN AND GIRLS IN BRITISH COLUMBIA (Canadian Journal of Native Studies, 2026)
Most knowledge about the Raven’s Nest People has tended to be predominantly speculative. To address this situation,this paper proposes a hypothesis that although still speculative, presents a probable explanation, even a compelling one, aboutthe ancestral origins of the Raven’s Nest Indigenous People. Further research and the gathering of stories including the oralhistory of the Raven’s Nest People will still have to be sought, from Elders of the Crow Nation, and other Indigenous tribesthat frequented the region of the Crowsnest Pass, however, it is hoped that this paper will provide the necessary foundation toadvance further research. The paper will conclude with a summary of the research and theories about the demise of both theKtunáxa and the Raven’s Nest Peoples.